CTIM-23. EVIDENCE OF T CELL ACTIVATION AND INTRATUMORAL NIVOLUMAB-PRESENCE IN GLIOBLASTOMA PATIENTS TREATED WITH NIVOLUMAB AND BEVACIZUMAB. (12th November 2021) - Skadborg, Signe; Maarup, Simone; Draghi, Arianna; Borch, Annie; Svane, Inge Marie; Hasselbalch, Benedikte; Poulsen, Hans; Lassen, Ulrik; Hadrup, Sine
Abstract: Glioblastoma (GBM) is an aggressive brain tumor with a dismal prognosis. Salvage neurosurgical resection is performed if possible and GBM patients are hereafter treated with Stupp's regime as standard treatment in the primary setting. However, after relapse, treatment in the recurrent setting shows very limited effect. We are monitoring the immune system of patients participating in a phase II clinical trial, where patients with recurrent GBM receive Nivolumab and Bevacizumab, treatments blocking PD1 and VEGF, respectively. The clinical trial consists of two arms. Arm A includes patients where surgical removal of the tumor is possible, and arm B includes patients who are only able to receive medical treatment. Arm A has received Nivolumab 7 days prior to surgery. Single cells suspension was produced from the resected tumors and blood samples was collected from patients through the course of treatment, wherefrom PBMCs (peripheral blood mononuclear cells) were purified. All samples were immunophenotyped using multi-color flow cytometry, to identify and follow the distribution of various immune cell types, and determine their expression of activating and inhibitory molecules over the course of treatment, in the periphery and in the tumor. An activated subset of T cells was characterized by CD103 (tissue residence), CD39 (antigen exposure) and CD69 (cytotoxicity). Such T cell populations were significantly enriched in the tumor. Importantly, we could demonstrate the presence of Nivolumab in the tumor, using an anti-IgG4 antibody to detect Nivolumab binding to T cells. We observed IgG4 positive T cell in the tumor digest, suggesting T cells binding Nivolumab are present in the tumor. Additional data analysis will be performed prior to the conference. With this we hope to gain further knowledge of the immune system's role in tumor clearance in the brain and the impact of immunotherapy hereupon.